Excavations at Portchester Castle. Volume II: Saxon - Cunliffe, Barry (Reports of the Research Committee of the Society of Antiquaries of London, 1976)
This is an account of excavations at Portchester Castle which took place under Barry Cunliffe in 1961-72. The volume deals with Saxon features and material recovered from these excavations. Included are descriptions of structures representing the Saxon occupation of the Roman fort and specialist reports on the material recovered, including pottery, coins, metalwork, human and animal bones, and archaeobotanical remains.